Contemporary Developments in Statistical Theory A Festschrift for Hira Lal Koul - Lahiri, Soumendra; Schick, Anton; SenGupta, Ashis; Sriram, T.N.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
This volume highlights Prof. Hira Koul$1 (Bs achievements in many areas of Statistics, including Asymptotic theory of statistical inference, Robustness, Weighted empirical processes and their applications, Survival Analysis, Nonlinear time series and Econometrics, among others. Chapters are all original papers that explore the frontiers of these areas and will assist researchers and graduate students working in Statistics, Econometrics and related areas. Prof. Hira Koul was the first Ph.D. student of Prof. Peter Bickel. His distinguished career in Statistics includes the receipt of many prestigious awards, including the Senior Humbolt award (1995), and dedicated service to the profession through editorial work for journals and through leadership roles in professional societies, notably as the past president of the International Indian Statistical Association. Prof. Hira Koul has graduated close to 30 Ph.D. students, and made several seminal contributions in about 125 innovative research papers. The long list of his distinguished collaborators is represented by the contributors to this volume.s
Preface -- Martingale estimating functions for stochastic processes -- On Hodges and Lehmann$1 (Bs 6 Result -- Acknowledgments -- List of Referees.s
Keywords: Statistics; Mathematics; Mathematical statistics; Statistics; Statistical Theory and Methods; Applications of Mathematics; Statistics, general